PENGEMBANGAN BUKU PEDOMAN PERMAINAN TRADISIONAL UNTUK MENUMBUHKAN KARAKTER KEBAIKAN HATI ANAK USIA 9-12 TAHUN - Nurma Dwi Astuti; Gregorius Ari Nugrahanta (Universitas Muhammadiyah Makassar, 2021)
The purpose of this study was to develop a traditional game manual to improve the heart character of children aged 9-12 years. This study used the ADDIE type of research and development (RD) method. This study involved nine elementary school teachers from various regions to conduct needs analysis, nine validators through expert judgments, and six children for limited trials of traditional game manuals. The results of the study showed that 1) Traditional game manuals to cultivate character improved the hearts of children aged 9-12 years based on ADDIE type steps, namely Analyze, Design, Develop, Implement, and Evaluate; 2) The quality of the traditional game manual was stated to be “Very good” with a score of 3.87 (scale 1-4) with the recommendation “No need for revision”; and 3) The application of traditional game manuals had an effect on children's heart character. The results of the significance test showed t(5) = 7,480; p = 0.001 (p 0.05). The magnitude of the influence of the guidebook was r = 0.95 or equivalent to 91.80% which was included in the